Proceedings of the 6th Computer Science On-line Conference 2017 (CSOC2017). Vol. 1, - Šilhavý, Radek; Šenkerřík, Roman; Oplatková, Zuzana; Prokopová, Zdeňka; Šilhavý, Petr (Springer, 2017)
This book presents new methods and approaches to real-world problems as well as exploratory research that describes novel artificial intelligence applications, including deep learning, neural networks and hybrid algorithms. This book constitutes the refereed proceedings of the Artificial Intelligence Trends in Intelligent Systems Section of the 6th Computer Science On-line Conference 2017 (CSOC 2017), held in April 2017.
Keywords: Artificial intelligence -- Congresses.; Intelligent control systems -- Congresses.; Neural networks (Computer science) -- Congresses.; elektronické knihy; electronic books